2017
DOI: 10.7883/yoken.jjid.2015.671
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute 2 Suppresses Japanese Encephalitis Virus Infection in <i>Aedes aegypti</i>

Abstract: SUMMARY: There are three main innate immune mechanisms against viruses in mosquitoes. Infection with the flavivirus dengue virus is controlled by RNA interference (RNAi) and the JAK-STAT and Toll signaling pathways. This study showed that another flavivirus, Japanese encephalitis virus (JEV), did not invade the salivary glands of Aedes aegypti and that this may be a result of the innate immune resistance to the virus. Argonaute 2 (Ago2) plays a critical role in the RNAi pathway. To understand the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…For many mosquito-borne flaviviruses, replication increases in Ae. aegypti or D. melanogaster in vitro as well as in vivo in the absence of an exo-siRNA response [11,21,44]. In addition, previous studies observed ZIKV-specific siRNAs in infected mosquito cells and increased ZIKV replication in a Dcr2 knockout cell line, which provided supporting evidence for the antiviral activity of the exo-siRNA pathway against ZIKV [16,46].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…For many mosquito-borne flaviviruses, replication increases in Ae. aegypti or D. melanogaster in vitro as well as in vivo in the absence of an exo-siRNA response [11,21,44]. In addition, previous studies observed ZIKV-specific siRNAs in infected mosquito cells and increased ZIKV replication in a Dcr2 knockout cell line, which provided supporting evidence for the antiviral activity of the exo-siRNA pathway against ZIKV [16,46].…”
Section: Discussionmentioning
confidence: 74%
“…The exo-siRNA pathway is the main antiviral defense pathway in mosquitoes, with Dcr2 and Ago2 having major roles [19,21,[42][43][44][45]. Silencing one of these key proteins during infection leads to an increase in viral replication for most arboviruses tested, including CHIKV, DENV and RVFV [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the findings on Jak-STAT signaling pathway associated with the encephalitis were also supported by previous reports. 19 21 …”
Section: Discussionmentioning
confidence: 99%
“…Also, exposure to sequential bites of uninfected mosquitoes altered the immune response favorably with increased participation of T-helper cells [ 41 ]. It is potentially possible that JE virus, which could be transmitted, by Culex and Aedes species [ 42 ] may also be interfered with human host immune response to D7 short forms. Indeed, in this context a concern would be the role of enhancing antibodies in the increased virulence of Dengue virus infection resulting in complications like Dengue hemorragic fever and Dengue shock syndrome.…”
Section: Discussionmentioning
confidence: 99%